Patients Perception and Knowledge on Dispensed Drugs: A Cross Sectional Study in Riyadh: Pharmaceutical Science-Clinical pharmacy for effective treatment - Renad Mohammed Sadek; Razan AL-Faifi; Muhra Al-Qahtani1; Munifah Alanizi; Arwa Sultan; Jowharah Awwad; Syed Mohammed Basheeruddin Asdaq (International Journal of Life Science and Pharma Research, 2022)
Patient’s knowledge of medicines and perception on health care services are paramount for high quality patient care. Despite their importance, there is lack of credible research reported from Riyadh city of Saudi Arabia to ascertain the present status on these issues. Therefore, current research was designed to elucidate the patients’ perception and knowledge on dispensed drugs in Riyadh Hospitals through a cross sectional study. A validated pre-tested questionnaire was used to check the knowledge and perception level of 247 patients visiting outpatient's pharmacies of different hospitals of Riyadh city during September to December 2018. The data obtained was analyzed by appropriate statistical tests using SPSS-IBM 23 statistical application. Most of the participants of the current study were in an age group of 16-35 years (64%) with 57% of them was graduates and (48%) were married. Further, 69% of them were employed and most of them (47%) were earning income ranging from 8000 to 15000 SAR/month. Furthermore, 86% of the surveyors were Saudi nationals, 91% were Riyadh city residents and 99.5% were Arabic speakers. Statistical analysis found a significant association between sociodemographic characteristics and knowledge level as well as their perception on health services such as pharmacists interaction, attitude, politeness and their knowledge. Most of the participants had an average to good knowledge on their dispensed drugs. In addition, we noted that there is a significant association between sociodemographic characteristics of patients and their perception on the health services which influence the patient's overall knowledge on their dispensed drugs. In conclusion, the patient’s knowledge on their dispensed medicines depends on factors associated with both patients and health care providers and good interaction between them increases the quality of health care services.